Spaceships and politics : the political theory of Rod Serling - Feldman, Leslie Dale (Lexington Books, 2010)
Spaceships and Politics: The Political Theory of Rod Serling examines the political themes in The Twilight Zone. In this unique show, Rod Serling used fantasy and the supernatural to explore political ideas such as capital punishment, the individual and the state, war, conformity, the state of nature, prejudice, and alienation. He used aliens and machines to understand human nature. While the themes in The Twilight Zone often reflected political concerns of the time, like the Cold War and post-industrial technology, the messages had broader political implications.